Experience of using anidulafungin for treatment of invasive candidosis in patients after liver transplantation - M. Sh. Khubutiya; N. K. Kuznetsova; S. V. Zhuravel; T. V. Chernenkaya; M. S. Novruzbekov; A. I. Bazhenov; I. I. Goncharova (Трансплантология (Москва))
This article is an example of a successful treatment invasive fungal infections and bacterial infections caused by multidrug-resistant pathogen after liver transplantation